Nocturnal oxygen desaturation in the late third trimester of uncomplicated pregnancy for prediction of late‐onset gestational hypertension. Issue 9 (26th July 2020) - Watanabe, Minako; Shinohara, Hitomi; Kodama, Hideya
Abstract: Aim: This study aimed to determine whether 1‐night screening of oxygen desaturation in women with uncomplicated pregnancy about 1 month before the due date is useful to predict late‐onset gestational hypertension (GH) after 37 weeks of gestation. Methods: We recruited 102 women with uncomplicated pregnancy between 34 and 36 weeks of gestation. These women then completed the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, and Berlin Questionnaire for obstructive sleep apnea, and recorded their oxygen saturation (SpO2 ) and physical acceleration profiles during nocturnal sleep for 1 night at home using a portable pulse oximeter and actigraph, respectively. Thereafter, their blood pressure was monitored weekly until delivery. Results: Pulse oximetry data between 34 and 36 weeks of gestation revealed that three women had an oxygen desaturation index (ODI) ≥5.0 and seven had a minimum SpO2 < 90%. During follow‐up until delivery, two women with an ODI ≥5.0 and a minimum SaO2 <90% developed GH at 37 weeks of gestation. Among clinical measures at recruitment, body mass index (BMI) and pulse oximetry measures appeared available for the prediction of GH. The positive predictive values (95% confidence intervals) of the criteria using these measures were 0.67 (0.26–0.67) for ODI ≥5.0, 0.29 (0.10–0.35) for minimum SpO2 <90%, and 0.07 (0.02–0.07) for BMI ≥25.0. Conclusion: For the prediction of late‐onset GH after 37 weeks of gestation, pulse oximetry measures about 1 month before the due date are particularly useful because of their high positive predictive values.